Implementation of the Collaborative Governance Model in Disaster Mitigation: A Process Analysis of the Regional Disaster Management Agency (BPBD) of Batu City - Wijayanto, Denis; Sjamsuddin, Sjamsiar; Suryadi, Suryadi (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Collaborative governance has become a crucial paradigm in complex disaster management, yet its implementation at the local level in Indonesia still faces various challenges. This study aims to comprehensively analyze the collaborative governance process in disaster mitigation management orchestrated by the Regional Disaster Management Agency (BPBD) of Batu City. Using a qualitative case study approach and the theoretical framework of the collaborative process by Ansell and Gash (2007), this research dissects the dynamics of cross-sectoral interactions. Data were collected through in-depth interviews with 13 key stakeholders from BPBD, related Regional Government Organizations (OPD), the Indonesian Red Cross (PMI), and the Disaster Risk Reduction Forum (FPRB), as well as through observation and document analysis. The findings reveal that the collaboration process in Batu City substantively operates through the five dimensions of the Ansell and Gash model: (1) Face-to-Face Dialogue is institutionalized through formal forums and accelerated by informal digital platforms; (2) Trust Building is catalyzed by facilitative leadership and intensive communication; (3) Commitment to the Process is manifested through routine activities and strong community participation; (4) Shared Understanding has been established at the community level but remains hindered by sectoral egos at the OPD level; and (5) Intermediate Outcomes, such as the formation of an active FPRB and shared knowledge products, have strengthened the legitimacy and momentum of the collaboration. This study concludes that while the collaborative model is effective at the operational and community levels, structural challenges at the bureaucratic level, particularly sectoral egos and human resource capacity gaps, are major impediments. The contribution of this article is to provide empirical validation and elaboration of the Ansell and Gash model in the Indonesian disaster context and to offer policy recommendations for strengthening local disaster governance. ‎